A Perspective of Accounting. - Herbert, Leo (The Accounting Review, 1971)
The article focuses on the influence accounting has had on the various elements of society. The significant roles those various elements have played on accounting should not be underestimated. For example, accounting, some writers say, had a considerable impact on the industrial revolution. Others have stated that the investment of great quantities of foreign capital in the U.S. after the Civil War had a consequential influence on what accounting is today. Accounting as a means for providing information for better government for the citizens of the U.S. is well accepted. But, the federal government also has played an essential role in providing an environment for the changing products of accounting. This influence, what the government has had on accounting and accounting on the government, can provide a perspective of accounting from a different viewpoint. In this paper, this perspective is seen from the standpoint of the many departments, agencies, and corporations of the federal government but with special reference to one agency, the U.S. General Accounting Office.